Othering in Children’s and YA Literature (Preučevanje otroške in mladinske književnosti, 2025)
Contemporary children’s and YA literature regularly explores topics such as disability and minority identities and personal circumstances. On the other hand, these topics and literary characters are still often labelled as “different/other” or “problems” (even “taboo”), especially in literary criticism. These, however, are categorisations that reinforce the established power relations and boundaries between the social norm and anything that deviates from it. They also perpetuate the (unconscious) prejudices and stereotypes implying that anything that does not conform to the majority worldview is somehow not normal or in need of the tolerance or sympathy of the majority population. The chapter analyses the practical use of the terms and interprets the findings with concepts from critical theory, in particular performativity (Austin, Butler), orientalism (Said) and epistemological violence (Spivak). It is critical of the terms, arguing against them even when they are used with good and (biblio)pedagogically optimistic intentions.